مقارنة فعالية تأثير مركّب (سالبوتامول - الابراتروبيوم بروميد ) مع فعاليّة السالبوتامول لوحده في معالجة الداء الرئوي الانسدادي المزمن - حجازية مالك; البرغوث مصطفى (Latakia University Journal -Medical Sciences Series, 2018)
يشكل COPD مشكلة مهمة من مشاكل الصحة العامة, و ينجم عن هذا المرض أعباء اجتماعية و اقتصادية كبيرة سواء على المريض وعائلته من جهة أو على الجهات الصحيّة المسؤولة عن العلاج من جهة أخرى. على الرغم من التطوّر الكبير في تدبير مرضى COPD , إلّا أنَّ إيجاد العلاج الأمثل من بين الخيارات العلاجية المطروحة ما يزال مدار بحث ويجب أن يتمتع بفوائد أكبر من الناحية السريرية و الاقتصادية سواء على المريض أو المؤسسات المسؤولة عن المريض . أجريت هذه الدراسة لمقارنة تأثير مشاركة (سالبوتامول مع الابراتروبيوم برومايد) مع تأثير السالبوتامول لوحده في علاج مرضى الداء الرئوي الانسدادي المزمن المستقر , من خلال مقارنة التحسن في قيمة كل من الحجم الزفيري الأقصى في الثانية الأولى (FEV1) و الحجم الزفيري الأقصى الكلي (السعة الحيوية القسرية) (FVC) بعد شهر من استخدام العلاج . اشتملت الدراسة على 80 مريض ( 53 ذكراً و 27 أنثى ) , و تراوحت أعمارهم بين (45 - 81) سنة , من بينهم (63) مريض مدخن و (17) مريض غير مدخن . أظهرت الدراسة أنه لدى المرضى الموضوعين لمدة شهر على مشاركة (سالبوتامول + إبراتروبيوم برومايد) كان التحسّن الحاصل في قيمة FEV1 (بمقدار 0.35 لتر) و في قيمةFVC (بمقدار 0.61 لتر) أعلى من التحسن الحاصل في قيمة FEV1 (بمقدار 0.28 لتر) و في قيمة FVC (بمقدار 0.48 لتر ) لدى المرضى الموضوعين لمدة شهر على العلاج بالسالبوتامول لوحده . COPD is a major public health problem , and it results with an extensive social and economical burden on both the patient and his family on one hand and the healthcare system on the other . Despite the great advances in the management of patients with COPD , the use of the optimal treatment of the proposed treatment options is still being discussed , and Must achieve greater benefit for both patients and the healthcare system . This research is designed to study and compare the effect of the combination (salbutamol and ipratropium bromide) with the effect of salbutamol alone in the treatment of patients with stable COPD , by studying and comparing the improvement in the forced expiratory volume in the first second (FEV1) and in forced vital capacity ( FVC) after a month of a treatment . The study included 80 patients (53 males and 27 females), the patients were between 45-81 years of age , 63 patients were smokers and 17 were nonsmokers. The study showed that after a month on therapy , for patients treated with the combination (salbutamol + ipratropium bromide) the increasing in FEV1 was 0.35 liters and in FVC was 0.61-liter , while , for the patients treated with salbutamol alone , the increasing in FEV1 was 0.28 liters and FVC was 0.48-liter . We concluded that a combination of ipratropium bromide and salbutamol is more effective at improving pulmonary function than salbutamol alone.